Structural grammatical meanings and proportions makes sense to her (Journal of the College of Basic Education, 2023)
Given the importance of the grammatical significance and its components; And the abundance of its sea and its meaning, we notice a scarcityIndependent terraces that deal with the meanings of syntax and syntax, and the head has reached a resonant grammarOn the authority of Ibn Jinni in his study of linguistic contexts, the verbal-linguistic context and the adverb context; anyElements constituting the verbal situation of a speaker or interlocutor or adverbs of the speaking personand the listener; And its rhodopsin remained - if any - are all elements related to lofty behaviorIbn Jinni was on a clear sinking in these aspects, as the evidence of the race of the case was shielded »and admonishedOn the link of speech with its circumstances; its proportions and circumstances; And clarify all of this to the recipient without confusion orgaz.For these and other things, this etc. came in an attempt to clarify the semantic conceptThe composition of Ibn Jinni, so he dealt with the inflectional meaning; And the moral and grammatical negligence and glamorThe meaning and the syntax" and the rank contradiction is the logical proportionality. And the validity of the meaning governs the shoutAlienation and the function of alienational movements; And other things related to the installation level.